Exploring Embodied Place Attachment Through Co‐Creative Art Trajectories: The Case of Mount Murals - Ruth Segers (Cogitatio, 2021)
The built and living environment in the Flemish region in Belgium is evolving noticeably. It is densifying at an ever‐faster pace and, along the way, becoming increasingly unfamiliar to its inhabitants. Many people face profound difficulties in autonomously and positively dealing with such drastic changes, causing their feeling of home to waver. Triggered by these challenges and supported by the local authority of a Flemish town, the experimental and co‐creative art project Mount Murals set out to stimulate new embodied interactions between and among local residents of various ages and backgrounds and with their built environment. These include remembering place‐related sentiments, being aware of body language that plays between participants while co‐creating and sensing an invigorating stimulus when seeing results. Awakening intrinsic appreciation in people for their own environment and associated social relationships stimulates an inclusive dealing with estranged relationships in space. Referring to the relational neuroscience principles attachment, co‐creating and co‐regulating as a modus of relational resonating, we explore how and under which conditions Mount Murals’ co‐creative art trajectory supports an evolving embodied place attachment, an essential element of the sense of belonging, in participants. By embedding assets inherent to art creation in action research and starting with meaningful everyday objects, Mount Murals carries forward an art expression that considers the co‐creation process and its co‐creative products as equally important.